2021
DOI: 10.3390/antibiotics10080941
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterials as a Successor of Antibiotics in Antibiotic-Resistant, Biofilm Infected Wounds?

Abstract: Chronic wounds are a growing problem for both society and patients. They generate huge costs for treatment and reduce the quality of life of patients. The greatest challenge when treating a chronic wound is prolonged infection, which is commonly caused by biofilm. Biofilm makes bacteria resistant to individuals’ immune systems and conventional treatment. As a result, new treatment options, including nanomaterials, are being tested and implemented. Nanomaterials are particles with at least one dimension between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 120 publications
0
8
0
Order By: Relevance
“…The nanoparticle's surface can be responsible for specific biofilm targeting by electrostatic interactions with the biofilm matrix, which favors the attachment of nanoparticles to the biofilm matrix and results in the release of the drug inside the biofilm [ 38 ]. In addition, the high surface area to volume ratio of nanoparticles allows for drug loading, which can result in strong antibiofilm efficacy [ 39 ]. The research found that thymol could inhibit biofilm formation and remove mature biofilms by inhibiting the production of polysaccharide intracellular adhesin (PIA) and the release of extracellular DNA (eDNA) [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nanoparticle's surface can be responsible for specific biofilm targeting by electrostatic interactions with the biofilm matrix, which favors the attachment of nanoparticles to the biofilm matrix and results in the release of the drug inside the biofilm [ 38 ]. In addition, the high surface area to volume ratio of nanoparticles allows for drug loading, which can result in strong antibiofilm efficacy [ 39 ]. The research found that thymol could inhibit biofilm formation and remove mature biofilms by inhibiting the production of polysaccharide intracellular adhesin (PIA) and the release of extracellular DNA (eDNA) [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the high surface area to volume ratio of nanoparticles allows for drug loading, which can result in strong antibioflm efcacy [39]. Te research found that thymol could inhibit bioflm formation and remove mature bioflms by inhibiting the production of polysaccharide intracellular adhesin (PIA) and the release of extracellular DNA (eDNA) [40].…”
Section: Discussionmentioning
confidence: 99%
“…For therapies of biofilm-associated skin disorders besides photodynamic therapy application of nanosized formulations including micelles, SLNPs or quatsomes can be used. In addition, ablation of the biofilm matrix can be achieved using NPs producing magnetic, photothermal, or photodynamic effects as a response to external stimuli [ 110 , 111 , 112 ]. The ability of antibiotic-resistant bacteria on wound surfaces enables their continuous growth, resulting in chronic wound infections and subsequently leading to the morbidity or even to mortality [ 113 ].…”
Section: Nanosystems and Their Benefitsmentioning
confidence: 99%
“…Among all the investigated metal-based NPs, those made of silver (silver nanoparticles, AgNPs) are the most widely studied nowadays. The antibacterial and antioxidant activity, as well as the efficacy of silver in the treatment of wounds, have been well-known for a long time, and even though its use was abandoned when antibiotics were discovered, nowadays, silver is once again receiving significant attention as an alternative to traditional antibiotics to overcome bacteria resistance issues [24,25]. In this scenario, silver nanotechnology has led to increased demand for its medical application, including the control of infections in wound dressings.…”
Section: Introductionmentioning
confidence: 99%